2000
DOI: 10.1111/j.1540-8175.2000.tb01149.x
|View full text |Cite
|
Sign up to set email alerts
|

Echocardiography Diagnosis of a Stenotic Double Orifice Parachute Mitral Valve with a Single Papillary Muscle

Abstract: We present the case of a patient with a single papillary muscle that is supporting both orifices of a stenotic double orifice mitral valve. With the use of both transthoracic and transesophageal echocardiography, we were able to prospectively define this entity, which was confirmed at surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…Six patients had both transthoracic echocardiography (TTE) and transesophageal echocardiography (TEE). An incremental diagnostic value of TEE has been described in two (Patients 3 and 4) 8,11 . In Patient 3, a preoperative TTE failed to diagnose PMV but intraoperative TEE diagnosed a PMV with a single papillary muscle 8 .…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Six patients had both transthoracic echocardiography (TTE) and transesophageal echocardiography (TEE). An incremental diagnostic value of TEE has been described in two (Patients 3 and 4) 8,11 . In Patient 3, a preoperative TTE failed to diagnose PMV but intraoperative TEE diagnosed a PMV with a single papillary muscle 8 .…”
Section: Resultsmentioning
confidence: 98%
“…An apical long‐axis view showed a typical parachute deformity of the mitral valve with a normal opening and common attachment of all the chordae. The chordae were elongated which was atypical—typically the chordae are shortened and thickened 11 . Two patients (Patients 1 and 2) 6,7 had the diagnosis of PMV made at autopsy.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously reported cases of DOMV had single or multiple papillary muscles. 3,4 However, previous echocardiography techniques had lower resolution; therefore, an accurate papillary muscle count could be determined only by open heart surgery or autopsy. In the present case, we could identify 2 complete sets of mitral valves including 4 papillary muscles and related structures by using a multimodal approach of TTE, heart dynamic computed tomography scan, and TEE.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, intraoperative transesophageal echocardiography was superior in defining the anatomy of the subvalvular apparatus with prospective identification of single papillary muscle that supported both mitral valve orifices with parachute phenomenon. 5) From the aspect of long-term prognosis, it is wellknown that mitral valvuloplasty is superior to mitral valve replacement. Zhou et al reported that thirty-day mortality was lower after mitral valvuloplasty compared to after mitral valve replacement.…”
Section: Discussionmentioning
confidence: 99%